2021
DOI: 10.4136/ambi-agua.2634
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite build-up effect on nitrous oxide emissions in a laboratory-scale anaerobic/aerobic/anoxic/aerobic sequencing batch reactor

Abstract: Biological wastewater treatment processes with biological nitrogen removal are potential sources of nitrous oxide (N2O) emissions. It is important to expand knowledge on the controlling factors associated with N2O production, in order to propose emission mitigation strategies. This study therefore sought to identify the parameters that favor nitrite (NO2-) accumulation and its influence on N2O production and emission in an anaerobic/aerobic/anoxic/aerobic sequencing batch reactor with biological nitrogen remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It is noteworthy that partial nitrification occurred in both the SBRs, whereas denitrification may not have been favored. Gomes et al (2021a) indicated that DO control is essential for total nitrification and denitrification and promoting TN removal, and Soliman et al (2016) demonstrated the importance of DO control in achieving partial nitrification. Ammonia nitrogen oxidation and nitrite accumulation were observed in both the SBRs.…”
Section: Sbr Performancementioning
confidence: 99%
“…It is noteworthy that partial nitrification occurred in both the SBRs, whereas denitrification may not have been favored. Gomes et al (2021a) indicated that DO control is essential for total nitrification and denitrification and promoting TN removal, and Soliman et al (2016) demonstrated the importance of DO control in achieving partial nitrification. Ammonia nitrogen oxidation and nitrite accumulation were observed in both the SBRs.…”
Section: Sbr Performancementioning
confidence: 99%